Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Model Kooperatif Tipe Stad Untuk Meningkatkan Hasil Belajar Kognitif Dan Afektif Pada Mata Pelajaran Pendidikan Pancasila Kelas IV - Liyanti, Ria; Juarsa, Osa; Widi Winarni, Endang (Jurnal Kajian Pendidikan Dasar, 2025)
This research aims to develop Student Worksheets (LKPD) based on the STAD Type Cooperative model to improve cognitive and affective learning outcomes in class IV Pancasila Education subjects. The method used in this research is Research and Development (R&D) with the ADDIE development model, which consists of five stages: analysis, design, development, implementation and evaluation. The type of research used by quasi-experimental researchers uses a posttest control group design. The type of data used is using question instruments and expert validation sheets. It is hoped that the developed LKPD used can help students understand the material, especially the fourth principle of Pancasila. The research results show that LKPD based on the STAD type cooperative model is effective in improving cognitive learning outcomes. This is necessary with the results of the T test (Independent Sample T Test) which shows a significant difference between the experimental class using LKPD with a mean of 89.33 and the control class with a mean of 39.33. Thus, LKPD based on the STAD type cooperative model can be used as appropriate teaching material to improve cognitive and affective learning outcomes in collaboration with the results of a percentage of respecting opinions of 86.67%, not forcing other people's will 86.67%, not criticizing other people's opinions 88.89% and not interrupting. other people's conversations.